Self-Access Learning in Chinese Language Using the “Greater Chinese” Mobile Application - Lee Mui Foong; Khor Gek Suan; Lee Sai Link (Penerbit USIM, 2025)
E-Proceedings International Language and Education Innovation Competition 2024 (I-INNOLED 2024) “Navigating The Future of Language And Education In A Transformative Era” 15-16 October 2024 Organized by : Faculty Of Major Language Studies Editors: Lubna Abd. Rahman, Amiliayanti Abd Halim, Maziahtusima Ishak